EMBRACING DISRUPTION: AN EMPIRICAL STUDY ON THE ACCEPTED PRACTICES AND STRATEGIC RESPONSES OF ENTREPRENEURS TO RAPID TECHNOLOGICAL ADVANCEMENTS - Sarkar, Debajyoti; Hara Kanta Nath (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This empirical research delves into the realm of entrepreneurial endeavors in the face of rapid technological advancements, exploring the accepted practices and strategic responses adopted by entrepreneurs as they navigate the disruptive landscape. In an era marked by continuous technological evolution, entrepreneurs are confronted with unprecedented challenges and opportunities. This study employs a rigorous empirical approach, integrating surveys, interviews, and case studies to shed light on the adaptive strategies and practices embraced by entrepreneurs in response to technological disruptions. The research aims to identify patterns and insights into how entrepreneurs perceive and respond to technological advancements, examining accepted industry practices and innovative strategies. By analyzing real-world case studies and gathering empirical evidence, the study seeks to contribute practical knowledge to the entrepreneurial community and inform policymakers about the evolving dynamics of technology-driven entrepreneurship.Furthermore, the research investigates the impact of these technological disruptions on various aspects of entrepreneurial ventures, including business models, market entry strategies, and organizational structures. By uncovering the accepted practices that lead to resilience and success, as well as the potential pitfalls, this study aims to provide a nuanced understanding of the interplay between entrepreneurs and rapid technological advancements. In essence, the findings of this research contribute to the ongoing discourse on entrepreneurship in the digital age, offering actionable insights for entrepreneurs, industry stakeholders, and policymakers alike. The study provides a roadmap for entrepreneurs to effectively navigate technological disruptions and seize opportunities for innovation and growth in an ever-changing business landscape.